History of the Origin of Piano in the Science of Instrument Performance - Z. Ziyavutdinova (International Journal on Integrated Education, 2021)
in this article, the appearance of the keyboard (piano) has a long history. The first musical instrument to appear in ancient Rome was the monochord. This instrument was in the form of a one-string box, which was gradually improved with the addition of wires. The article explains how his keys were created, who invented them and named the instrument "Piano". It was later reported that the instruments of the clavichord and clavichord were gradually phased out.